Advanced parental age and autism risk in children: a systematic review and meta‐analysis. (14th November 2016) - Wu, S.; Wu, F.; Ding, Y.; Hou, J.; Bi, J.; Zhang, Z.
Abstract : Objective: Advanced parental age has raised additional concern as a risk factor of autism. We conducted a meta‐analysis of observational studies investigating the association between advanced parental age and risk of autism. Method: PubMed, EMBASE, and Web of Science were searched for reports published up to November 11, 2015. Risk estimates from individual studies were pooled using random‐effects models. Results: Twenty‐seven studies were included in the meta‐analysis. Compared with the reference points, the lowest parental age category was associated with a reduced risk of autism in the offspring, with adjusted odds ratios (ORs) 0.89 (95% confidence intervals [CIs] 0.75–1.06) and 0.81 (95% CI 0.73–0.89) for mother and father, respectively, and the highest parental age category was associated with an increased risk of autism in the offspring, with adjusted ORs 1.41 (95% CI 1.29–1.55) and 1.55 (95% CI 1.39–1.73) for mother and father respectively. Dose–response meta‐analysis indicated that an increase of 10 years in maternal and paternal age was associated with an 18% and 21% higher risk of autism. Conclusion: Advanced parental age was associated with an increased risk of autism in the offspring. More mechanistic studies are needed to further explain this positive association.